2015
DOI: 10.1016/j.jmau.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic studies on the Y organ of the freshwater crab Travancoriana schirnerae

Abstract: The fine structure of the premoult Y organ in the freshwater crab Travancoriana schirnerae revealed elliptical epithelial gland cells with large, eccentric, multinucleolated nuclei and ample cytoplasm. The cytoplasm showed numerous polymorphic mitochondria with tubular cristae, highly anastomosed tubules and vesicles of smooth endoplasmic reticulum (SER), rich free ribosomes, small amounts of cisternae of rough endoplasmic reticulum (RER), microtubules and was devoid of Golgi complexes. Mitochondria were of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The mitochondria due to its unique highest membrane structure packing per volume are ideal object for such study. This is due to the presence of cristae, the mitochondrial inner membrane structure, ranging in size from 100 to 500 nm 5153 . Two cell types, a human cancer and non-cancerous animal, were chosen for our experiments, correspondently human colorectal cancer cell line HCT116 (ATCC CCL-247TM, Manassas, VA, USA) and the Chinese hamster ovary cell line CHO-K1 cells (ATCC CCL-61TM, Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondria due to its unique highest membrane structure packing per volume are ideal object for such study. This is due to the presence of cristae, the mitochondrial inner membrane structure, ranging in size from 100 to 500 nm 5153 . Two cell types, a human cancer and non-cancerous animal, were chosen for our experiments, correspondently human colorectal cancer cell line HCT116 (ATCC CCL-247TM, Manassas, VA, USA) and the Chinese hamster ovary cell line CHO-K1 cells (ATCC CCL-61TM, Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Travancoriana schirnerae Bott, 1969 is an edible freshwater crab commonly distributed in the wetlands of Wayanad, Kerala, India. Previous studies on ultrastructure of the premoult YO of this species have shown numerous polymorphic mitochondria with tubular cristae, highly anastomosed tubules and vesicles of SER and abundant free ribosomes (Sudha Devi et al, 2015). Further studies on moult cyclerelated and destalked crab YO histology in the same species revealed cellular hypertrophy, cytoplasmic granulations and secretory vesicles (Smija and Sudha Devi, 2016).…”
Section: Effect Of 20e and Mf On Y-organ Histomorphologymentioning
confidence: 83%